3D QSAR Analysis of PPAR-γAgonist and PTPIB Antagonist as Anti-hyperglycemic Agents - KAPOOR, SHWETA; GARG, GOPAL; SARAF, SWARNLATA (Asian Journal of Chemistry, 2010)
A quantitative structure activity relationship studies were observed on series of N-(2-benzoylphenyl)-L-tyrosine for Peroxisome Proliferator Activated Receptor (PPARγ) agonist and new azolidinediones for Protein Tyrosine Phosphatase 1B (PTP1B) antagonist. Various physicochemical parameters were calculated by chem 3D Ultra version 6.0. Several statistical regression expressions were obtained by using multiple regression analysis. Steric descriptor (PMI-X, Ovality, CMA, PMI-Z); electronic descriptor (DD, total energy); and thermodynamic descriptor (Gibb's energy, HF) were found to have significant correlation ship in both of the series. Value of correlation coefficient (r) in series 1 is found to be 0.799, statistical significance is 99 % and in series 2 r = 0.869, statistical significance is 99.9 %.